Teoretski koncepti, družboslovne raziskave ter izzivi za izkoreninjenje pojava trpinčenja med in nad zaposlenimi v zdravstveni negi - Robnik, Sonja (Obzornik zdravstvene nege, 2012)
Introduction: Workplace bullying is an important issue that is growing in significance. In Slovenia, nursing was the first occupational group that has made some important steps towards recognition, prevention and elimination of violence among and against its members. Recognition, transparency and in-depth studies are the main future challenges. The aim of the article is to present the key theoretical concepts and sociological research of workplace bullying in Slovenia and abroad. Methods: Literature review as a descriptive research method was used in the study. 31 out of 282 selected references are further analysed, 16 including basic definitions of bullying and 15 presenting useful and applicable research results. Discussion and conclusion: In defining workplace bullying, three main obstacles are encountered. There is no legal or official definition of bullying within the European Union; the subtle nature of workplace bullying makes it harder to be recognized within the temporal and environmental context - the behavior is covert. In addition, the same phenomena have been described differently, yielding no international comparison of the relevant research results. Some common points, however, can be discerned. Bullying is about violence but a single violent act cannot be marked as bullying.
Keywords: dignity; dostojanstvo; hostile work evironment; nasilje na delovnem mestu; raziskave; social interactions; socialne interakcije; trpinčenje; workplace violence; zdravstvena nega